Development of athletes` psychophysiological condition monitoring system based on cloud technologies - Korotkov, K. G. (Theory and Practice of Physical Culture, 2021)
Presented a description of the principles of operations of a system for monitoring the psychophysiological condition of athletes on the basis of cloud technologies developed in SPbRIPC. The system is based on the method of gas-discharge visualization included in the list of FMBA devices for monitoring the psychophysiological condition of athletes. The software is implemented on the server, which provides an opportunity to work in any conditions, both in the training hall and in the field, automatic storage of the received information, access to the database only for authorized users and high security of the database. The developed system allows working with the database from any computer or mobile phone connected to the Internet. Experience of 5 years of operation of the system has shown that it has a high degree of reliability, speed, convenience for users, and for all this time there have been no cases of information leakage or loss.